1999
DOI: 10.1002/(sici)1097-0215(19990412)81:2<174::aid-ijc2>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber and plant foods in relation to colorectal cancer mortality: The Seven Countries Study

Abstract: Many observational studies have found that higher consumption of vegetables, and to a lesser extent of fruits, was associated with lower risk of colorectal cancer. In particular, fiber or foods high in fiber have received attention in the potential prevention of colorectal cancer. We performed an ecological analysis with data of the Seven Countries Study, to investigate whether intake of fiber and plant foods contributes to cross-cultural differences in 25-year colorectal-cancer mortality in men. In the Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Results from another large case-control study (1953 cases) in Italy also reported a significant reduction in risk of colorectal cancer associated with high dietary vitamin B6 intake (≥ 2.78 mg/d) [9]. In a between-country comparison designed to evaluate the role of plant foods in relation to colorectal cancer mortality [10], higher vitamin B6 intake was statistically significantly associated with lower mortality from colorectal cancer, after adjustment for energy and meat intake.…”
Section: B Vitaminsmentioning
confidence: 91%
“…Results from another large case-control study (1953 cases) in Italy also reported a significant reduction in risk of colorectal cancer associated with high dietary vitamin B6 intake (≥ 2.78 mg/d) [9]. In a between-country comparison designed to evaluate the role of plant foods in relation to colorectal cancer mortality [10], higher vitamin B6 intake was statistically significantly associated with lower mortality from colorectal cancer, after adjustment for energy and meat intake.…”
Section: B Vitaminsmentioning
confidence: 91%
“…Caygill et al [2], in their ecologic analysis of FAO food consumption described under "Vegetables," above, found cereal consumption to be highly protective against colorectal cancer in both male and female subjects when the cereal is consumed at the present time; cereal levels consumed 20 years ago were also found to be protective for female subjects [2]. In contrast, investigators from the Seven Countries Study, based on analysis of meal composites from 16 cohorts, found no relation of grain consumption to colorectal cancer risk [17]. A recent US case-control study of colon cancer [5] showed an OR of 0.47 (0.25-0.91) for consumption of total cereals (cold and hot), and among men a similar OR was found for intake of breads and cereals (OR=0.43 [0.22-0.82]).…”
Section: Cerealsmentioning
confidence: 98%
“…(average dietary fiber intake among US adults is 12-16 g/d). In the Seven Countries Study [17], fiber was highly related to colorectal cancer mortality. The mortality rate ratio for a 10% change in mean daily fiber intake was 0.89 (0.80-0.97), with an increase of 10 grams of fiber daily associated with 33% lower 25-year colorectal cancer mortality.…”
Section: Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…No association was observed between colorectal cancer and fruit and vegetable consumption for any frequency or type of food (RR, 1.08; 95% CI 0.84-1.38) for consumption of at least 6 servings of fruits and vegetables per day compared to 2 or fewer servings. An ecological analysis of data from the Seven Countries Study, which included groups from across Europe, the United States, and Japan, and represented 12,763 men aged 40 to 59 years old demonstrated no association of plant foods (fruits, vegetables, potatoes, and grains obtained from a one-week dietary history) and colorectal cancer incidence (P=0.183) [5]. [7].…”
Section: Fruits and Vegetablesmentioning
confidence: 99%